Strategi Guru PAI Dalam Membentuk Karakter Peduli Sosial Siswa Melalui Metode Pembiasaan Jum’at Berinfaq di SMA - Lutfiyatul Amaliyah, Evi Diani; Mardliyah, Layla (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The character of social care is one of the characters formed through the habituation method, namely Friday almsgiving. This study aims to describe and analyze the strategy of Islamic Religious Education teachers in forming student’s social care character through the habituation method of Friday almsgiving at SMA Negeri 1 Randudongkal Pemalang. The research method used is a case study with a qualitative approach. Data were collected through observation, interviews with the principal, Islamic Religious Education teachers and students, and documentation of friday almsgiving activities. Using data analysis such as data collection, data reduction, data presentation, and drawing conclusions. For data validity, triangulation techniques were used. This study produced the following description that the character of social care includes exemplary behavior, namely Islamic Religious Education teachers participate in giving alms. Discipline, namely Islamic Religious Education teachers monitor and assist in the implementation of almsgiving activities, make schedules and reports related to almsgiving activities. Habituation through Friday almsgiving activities using four methods includes routine activities, namely the habituation of Friday almsgiving is carried out routinely every Friday. Spontaneous activities carried out include visiting friends who are sick or paying condolences when a student’s guardian dies. The role meodel carried out is the Islamic Religious Education teachers participate in giving alms. The programmed activities carried out are sacrificial practice. The habit of giving alms on Fridays can have a positive impact on students, such as being more concerned about others and being wiser in managing money.